A Comparison of Tactile Sensors for In-Hand Object Location. (21st January 2016) - Fernandez, Raul; Vazquez, Andres S.; Payo, Ismael; Adan, Antonio
Abstract : This work presents an extensive analysis of the usefulness of tactile sensors for in-hand object localization. Our analysis is based on a previous work where we proposed a method for the evaluation of tactile data using two algorithms: a Particle Filter algorithm and an Iterative Closest Point algorithm. In particular, we present a comparison of six different sensors, including two pairs of sensors based on similar technology, showing how the design and distribution of tactile sensors can affect the performance. Also, together with previous results where we demonstrated the importance of the synergy between tactile data and hand geometry, we corroborate that it is possible to obtain more similar performance with a simple fingertip sensor, than with more complex and expensive tactile sensors.